Treatment Approach for A Rare Case of Cervical Cancer in Pregnancy : Pendekatan Terapi pada Kanker Serviks dalam Kehamilan - Yuannita I. Putri; Gumilang Wiranegara (Indonesian Journal of Obstetrics and Gynecology, 2022)
Abstract Objective: To add a new overview of cervical cancer in pregnancy and to review several treatment approaches using available guidelines. Methods: Case report. Case: A 29 years old woman, gravida 3 para 2 in 10 weeks of pregnancy, was presented with vaginal bleeding and bloody vaginal discharge. Ultrasound examination showed a 10 weeks single live intrauterine fetus and a mass on the cervix. The histopathological report revealed a poorly differentiated cervical adenocarcinoma without invasion of lymphovascular space. Patient was diagnosed with cervical carcinoma FIGO stage IB3 in 10 weeks of pregnancy. The patient opted to unpreserved the pregnancy. Radical hysterectomy with fetus in situ and bilateral pelvic lymphadenectomy was performed. Patient was referred to undergo adjuvant radiation therapy. Conclusion: Cervical cancer in pregnancy is a rare and special condition that requires individual planning for the diagnostic and treatment approaches. Keywords: cervical cancer, cervical cancer in pregnancy, fetus in situ hysterectomy, pregnancy, radical hysterectomy. Abstrak Tujuan: Untuk menambah gambaran kasus mengenai kanker serviks dalam kehamilan serta membahas pendekatan terapi menggunakan pedoman – pedoman yang ada. Metode: Laporan kasus. Kasus: Seorang perempuan berusia 29 tahun dengan G3P2 usia kehamilan 10 minggu datang dengan keluhan perdarahan pervaginam dan keputihan bercampur darah. Hasil dari USG menunjukkan adanya janin berusia 10 minggu serta massa pada serviks. Hasil pemeriksaan histopatologi menunjukkan adanya adenokarsinoma serviks berdiferensiasi buruk tanpa invasi limfovaskuler. Pasien didiagnosis dengan kanker serviks stadium FIGO IB3 dalam kehamilan 10 minggu. Pasien setuju untuk dilakukan terminasi kehamilan. Pada pasien kemudian dilakukan laparotomi histerektomi radikal dengan fetus in situ serta limfadenektomi pelvik bilateral. Pasien kemudian dirujuk untuk dilakukan terapi ajuvan dengan radiasi. Kesimpulan: Kanker serviks pada kehamilan merupakan suatu kondisi khusus sehingga perencanaan diagnostik dan manajemen terapi membutuhkan perencanaan secara individual di setiap kasusnya. Kata kunci: Kanker, kanker serviks, kanker serviks dalam kehamilan, kehamilan, , histerektomi radikal, histerektomi dengan fetus in situ.